Estimating Source Region Influences on Black Carbon Abundance, Microphysics, and Radiative Effect Observed Over South Korea. Issue 23 (4th December 2018) - Lamb, Kara D.; Perring, Anne E.; Samset, Bjørn; Peterson, Dave; Davis, Sean; Anderson, Bruce E.; Beyersdorf, Andreas; Blake, Donald R.; Campuzano‐Jost, Pedro; Corr, Chelsea A.; Diskin, Glenn S.; Kondo, Yutaka; et al.
Abstract: East Asia is the strongest global source region for anthropogenic black carbon (BC), the most important light‐absorbing aerosol contributing to direct radiative climate forcing. To provide extended observational constraints on regional BC distributions and impacts, in situ measurements of BC were obtained with a single particle soot photometer during the May/June 2016 Korean‐United States Air Quality aircraft campaign (KORUS‐AQ) in South Korea. Unique chemical tracer relationships were associated with BC sourced from different regions. The extent and variability in vertical BC mass burden for 48 profiles over a single site near Seoul were investigated using back trajectory and chemical tracer analysis. Meteorologically driven changes in transport influenced the relative importance of different source regions, impacting observed BC loadings at all altitudes. Internal mixing and size distributions of BC further demonstrated dependence on source region: BC attributed to China had a larger mass median diameter (180 ± 13 nm) than BC attributed to South Korea (152 ± 25 nm), and BC associated with long‐range transport was less thickly coated (60 ± 4 nm) than that sourced from South Korea (75 ± 16 nm). The column BC direct radiative effect at the top of the atmosphere was estimated to be 1.0 − 0.5 + 0.9  W/m 2, with average values for different meteorological periods varying by a factor of 2 due to changes in the BC vertical profile. During the campaign, BC sourced from South Korea (≤ 31%), China (22%), and Russia (14%) were the most significant single‐region contributors to the column direct radiative effect. Key Points: Black carbon vertical profiles observed in late spring 2016 in South Korea were consistent with strong regional sources The profiles systematically measured over a single site varied due to meteorologically driven changes in transport South Korea, China, and Russia were the major source region contributors to black carbon column direct radiative effect